Unequal Assignment and Unequal Promotion in Job Ladders - Winter-Ebmer, Rudolf; Zweimüller, Josef (Journal of Labor Economics, 1997)
In this study gender differentials in professional status attainment are analyzed. In the theoretical literature, unequal treatment of females is often rationalized by their higher probability of quitting. To test this hypothesis empirically we use data from the Austrian microcensus and find that neither the risk of childbearing nor different productive characteristics can explain the crowding of females in lower hierarchical positions. Females have to fulfill higher ability standards to be promoted; work experience is not rewarded in the same manner as it is for men.